Moral Values Derived from the Interpretation of the Story of Moses (PBUH) and the Family of Shu‘ayb (Journal of Imam Al-Kadhim College, 2025)
This research investigates the ethical values embedded in the story of Prophet Moses and the family of Shu‘ayb (peace be upon them), as narrated in Surah Al-Qasas. The study provides an in-depth analytical examination of the Qur’anic text with the aim of uncovering the moral and pedagogical dimensions inherent in the narrative. Qur’anic stories are not merely historical accounts or literary expressions; rather, they serve as profound educational tools that reflect divine wisdom in guiding human behavior and nurturing ethical conduct.The study highlights a number of prominent values illustrated through the events and characters of the story—such as courage in the face of adversity, modesty as a noble feminine virtue, generosity and kindness toward strangers, and trustworthiness and honesty as foundational traits in interpersonal relations. These values are extracted from the Qur’anic context and are then analyzed for their relevance and applicability in contemporary educational and social settings.The research adopts two core methodologies: the analytical method, which focuses on examining the Qur’anic verses in depth to elucidate their ethical significance, and the inferential method, which aims to derive practical educational applications from the extracted values. The study ultimately seeks to emphasize the role of prophets and righteous individuals as exemplary moral figures and to demonstrate how Qur’anic ethical principles can contribute to the development of a morally grounded and spiritually balanced human character in today’s world.
Keywords: Moral values, Surah Al-Qasas, Prophet Moses, Family of Shu‘ayb, Qur’anic education, Analytical method, Islamic pedagogy; Moral values; Surah Al-Qasas; Prophet Moses; Family of Shu‘ayb; Qur’anic education; Analytical method; Islamic pedagogy